2019
DOI: 10.1016/j.arabjc.2014.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic wet air oxidation of phenol over ultrasound-assisted synthesized Ni/CeO2–ZrO2 nanocatalyst used in wastewater treatment

Abstract: Non-noble metal Ni with different loadings was coated on precipitated CeO 2 -ZrO 2 support by the sonochemistry method and examined for catalytic wet air oxidation of phenol. The structure of the nanocatalysts was determined by BET, FESEM, XRD, and FTIR analyses. The results showed non-uniform morphology of the nanocatalyst at lower Ni contents changed to homogenous morphology with spherical nano particles at higher Ni contents. While the size of NiO crystals remained constant with rising Ni content, the cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 46 publications
(52 reference statements)
0
5
0
Order By: Relevance
“… 40–44 Ni has been used mainly for steam reforming reactions, and poorly for oxidation reactions. 45–49 However, to our knowledge using Ni/Al 2 O 3 , NiCeO 2 and Ni/Al 2 O 3 –CeO 2 catalysts with nano characteristics for the catalytic wet air oxidation of phenol in milder conditions has not been reported in the literature, so there was enthusiasm to investigate this nano structured system.…”
Section: Introductionmentioning
confidence: 99%
“… 40–44 Ni has been used mainly for steam reforming reactions, and poorly for oxidation reactions. 45–49 However, to our knowledge using Ni/Al 2 O 3 , NiCeO 2 and Ni/Al 2 O 3 –CeO 2 catalysts with nano characteristics for the catalytic wet air oxidation of phenol in milder conditions has not been reported in the literature, so there was enthusiasm to investigate this nano structured system.…”
Section: Introductionmentioning
confidence: 99%
“…Its ability to store and release oxygen due to the effective redox Ce 4+ /Ce 3+ sites that enable the exchange of oxygen via oxygen vacancy significantly increases the performance of catalytic systems and suppresses the deactivation of catalysts under rigorous reaction conditions [ 57 , 58 ]. For the degradation of refractory organic compounds (ROCs), it has been reported that the oxygen storage capacity (OSC) and the redox properties of ceria should be increased by the introduction of other transition and nontransition metal ions; therefore, many ceria-based catalysts have been developed, such as CeO 2 -ZrO 2 [ 57 , 58 , 59 , 60 , 61 ], CeO 2 -TiO 2 [ 62 , 63 , 64 ], CeO 2 -WO 3 [ 65 ], CeO 2 /Al 2 O 3 [ 66 , 67 ] and CeO 2 -SiO 2 [ 68 , 69 , 70 ]. Besides, the species Ti 3+ for the TiO 2 support is related to oxygen vacancies as a result of lattice distortion or surface defects [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…The bands between 400 and 500 cm −1 correspond to Ni-O stretching 73 and Ni-O-Ni bond. 74 The CO 2 methanation performance of the reduced samples is evaluated at 400 °C (Fig. 6).…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%